Synthesis and biological activity of 5-chloro-N(4)-substituted phenyl-9H-pyrimido[4,5-b]indole-2,4-diamines as vascular endothelial growth factor receptor-2 inhibitors and antiangiogenic agents(1) - Gangjee, Aleem (2013)
Inhibition of receptor tyrosine kinase (RTK) signaling pathways is an important area for the development of novel anticancer agents. Numerous multikinase inhibitors (MKIs) have been recently approved for the treatment of cancer. Vascular endothelial growth factor receptor-2 (VEGFR-2) is the principal mediator of tumor angiogenesis. In an effort to develop ATP-competitive VEGFR-2 selective inhibitors the 5-chloro-N(4)-substituted phenyl-9H-pyrimido[4,5-b]indole-2,4-diamine scaffold was designed. The synthesis of the target compounds involved N-(4,5-dichloro-9H-pyrimido[4,5-b]indol-2-yl)-2,2-dimethylpropanamide) as a common intermediate. A nucleophilic displacement of the 4-chloro group of the common intermediate by appropriately substituted anilines afforded the target compounds. Biological evaluation indicated that compound 5 is a potent and selective VEGFR-2 inhibitor comparable to sunitinib and semaxinib.